The Impact of Fly Over Construction at Simpang Ramayana Mall in An Effort to Reduce Traffic Logs and Community Economic Growth in Tanjungpinang City - Wartono, Wartono; Sidabutar, Yuanita FD; Indrawan, Mohamad Gita; Panusunan, Panusunan (Graduate Program Magister Manajemen Pendidikan, 2023)
This is descriptive research that describes the characteristics of the population or phenomenon being studied. So that this one research method is the main focus is to explain the object of research. The purpose of this study is to try to reduce the number of vehicles that use the DI road. The research method focuses more on discussing why an event or phenomenon occurs. The results described the construction of the fly over at the Ramayana intersection in Tanjungpinang City is a design whose goal is to try to prevent traffic jams from occurring at that location and to make travel time efficient so as to minimize the impacts such as wasted time due to traffic jams.